Wireless Sensor Network (International Journal of Engineering and Computer Science, 2017)
The history of sensor network technology originates in the first distributed sensing idea implementations. The continuous work ofresearchers and engineers over sensor networks which lately became wireless sensor networks (WSNs). Wireless sensor networkis one of the g r owi n g technology for sensing and performing the different tasks. Such networks are beneficial in manyfields, such as emergencies, health monitoring, environmental control, military, industries and these networks prone to malicioususers' and physical attacks due to radio range of network, un-trusted transmission, unattended nature and get accesseasily. Security is a fundamental requirement for these networks. In this paper, our center of attention is on physical attacksand issues in wireless sensor networks. Through this review, easily identify the purpose and capabilities of the attackers. Further,we discuss well-known approaches of security detection against physical attacks. The template is used to format your paper andstyle the text. All margins, column widths, line spaces, and text fonts are prescribed; please do not alter them.